EXPLORING THE ANTECEDENTS OF RISKY CREDIT BEHAVIOR IN MSMES: THE IMPACT OF FINANCIAL LITERACY, SELF-FRAMING CONTROL, AND FINANCIAL STRESS - Purwaningtyas, Putri; Rahajuni, Dijan; Rafinda, Ascaryan; Barika, Christian Rotimi (Performance: Jurnal Personalia, Financial, Operasional, Marketing dan Sistem Informasi, 2025)
The attractive development of Financial Technology triggers the potential risky credit behavior and it raises concerns over the potential for increased credit risk, especially for MSMEs. The financial literacy raise as the critical factor related to the financial decision, including credit decision. However, the interaction mechanism between financial literacy and risky credit behavior is inadequately comprehended. Based on the Prospect Theory posits the psychological effect can influence the decision making process. This study investigates the mediating effect of self-framing control to explain the mechanism and financial stress to explain the certain circumtance with the relation of risky credit behavior, using 129 respondents of MSMEs in Banyumas Region. The result indicate the financial literacy have negative impact to risky credit behavior and mediate by self-framing control to explain those mechanism. In addition, the high level of financial stress stimulate the higher risky credit behavior. This study contributes to financial literacy literature by identifying the interplay of self-framing control, financial literacy, and credit behavior.